A Comparative Evaluation of the Distribution of Concanavalin A-Binding Sites on the Surfaces of Normal, Virally-Transformed, and Protease-Treated Fibroblasts - Rosenblith, J. Z. (1973)
The topographical distributions of concanavalin A-binding sites on the surfaces of 3T3, proteasetreated 3T3, and simian virus 40-transformed 3T3 cultured mouse fibroblasts appear to be different, as shown by a shadow-cast replica technique using concanavalin A and a hemocyanin marker, or as shown previously on isolated membranes with concanavalin A coupled to ferritin. However, chemical fixation of cells before labeling with concanavalin A and hemocyanin, or labeling exclusively at 4°, allows one to distinguish between inherent concanavalin A-binding-site topography and potential rearrangement of sites induced by the action of the multivalent concanavalin A molecule itself. The inherent distribution of binding sites on 3T3, protease-treated 3T3, and transformed cells is actually the same on all cells, i.e., dispersed and random. Treatment of unfixed transformed or protease-treated 3T3 cells, but not normal 3T3 cells, with concanavalin A and hemocyanin at 37° (or at 4° with subsequent warming to 37°), however, results in clustering of binding sites, presumably due to crosslinking of neighboring lectin-binding sites by the quadrivalent concanavalin A. Thus, the underlying difference between concanavalin A-binding sites on normal as compared with transformed or protease-treated normal cells lies not in the inherent topography of binding sites, but rather in the susceptibility of the sites to aggregation by concanavalin A. The latter may reflect an increased mobility of lectin-binding sites on transformed or protease-treated cells.